2022
DOI: 10.1002/adma.202203920
|View full text |Cite
|
Sign up to set email alerts
|

Interspace and Vacancy Modulation: Promoting the Zinc Storage of an Alcohol‐Based Organic–Inorganic Cathode in a Water–Organic Electrolyte

Abstract: Expanding interspace and introducing vacancies are desired to promote the mobility of Zn ions and unlock the inactive sites of layered cathodes. However, this two‐point modulation has not yet been achieved simultaneously in vanadium phosphate. Here, a strategy is proposed for fabricating an alcohol‐based organic–inorganic hybrid material, VO1−xPO4·0.56C6H14O4, to realize the conjoint modulation of the d‐interspace and oxygen vacancies. Peculiar triglycol molecules with an inclined orientation in the interlayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…[ 17 ] It is observed that VOPO 4 @G‐Air exhibits a higher resonance amplitude than that of VOPO 4 @G‐O 2 (Figure 1i), indicating a higher concentration of V 4+ in VOPO 4 @G‐Air. [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] It is observed that VOPO 4 @G‐Air exhibits a higher resonance amplitude than that of VOPO 4 @G‐O 2 (Figure 1i), indicating a higher concentration of V 4+ in VOPO 4 @G‐Air. [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
“…Dramatic progress has been accomplished in the pursuit of high performance cathode materials such as transition metal (manganese, vanadium) oxide, organic molecule, and so on. [1][2][3][4][5] Nevertheless, unbounded dendrite growth, corrosion and passivation of zinc (Zn) metal anodes, resulting in low coulombic efficiency (CE) and limited lifetime, which may lead to battery short circuit, is one of the most crucial obstacles for the development of aqueous ZIBs. [6][7][8][9][10][11][12] Several strategies have been executed to enhance the electrochemical stability of Zn metal anodes by inhibiting the dendrite formation and banishing the water-induced parasitic reaction, including electrolyte regulation, interfacial manipulation, substrate modification, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous rechargeable zinc‐ion batteries (ZIBs) are regarded as one of the most competitive candidates for large‐scale energy storage due to their high safety, low cost and environmental friendliness, and have become a research hotspot in recent years. Dramatic progress has been accomplished in the pursuit of high performance cathode materials such as transition metal (manganese, vanadium) oxide, organic molecule, and so on [1–5] . Nevertheless, unbounded dendrite growth, corrosion and passivation of zinc (Zn) metal anodes, resulting in low coulombic efficiency (CE) and limited lifetime, which may lead to battery short circuit, is one of the most crucial obstacles for the development of aqueous ZIBs [6–12] .…”
Section: Introductionmentioning
confidence: 99%
“…3–6 Therefore, the modification of inorganic intercalation (mostly using metal ions such as Li + , Na + , K + , and Al 3+ , and NH 4 + ) has been adopted to address this problem, producing numerous intercalated vanadium oxides such as Li x V 2 O 5 · n H 2 O, 7 Na x V 2 O 5 · n H 2 O, 8 K 0.5 V 2 O 5 ·0.76H 2 O, 9 Al–V 2 O 5 , 10,11 NVO 12 etc. On the other hand, organics are also frequently used for intercalation, including polyaniline, 13 polypyrrole, 14 and various small molecules (ethylenediamine, 15 triethylene glycol, 16 dodecyl amine, 17 etc. ).…”
mentioning
confidence: 99%
“…to address this problem, producing numerous intercalated vanadium oxides such as Li 9 Al-V 2 O 5 , 10,11 NVO 12 etc. On the other hand, organics are also frequently used for intercalation, including polyaniline, 13 polypyrrole, 14 and various small molecules (ethylenediamine, 15 triethylene glycol, 16 dodecyl amine, 17 etc.). However, these attempts have tried to regulate the zinc ion transport by changing the layer spacing, which has no benefit for capacity enhancement.…”
mentioning
confidence: 99%